User Modeling, Adaptation, and Personalization 21th International Conference, UMAP 2013, Rome, Italy, June 10-14, 2013 Proceedings - Carberry, Sandra; Weibelzahl, Stephan; Micarelli, Alessandro; Semeraro, Giovanni; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the thoroughly refereed proceedings of the 21st International Conference on User Modeling, Adaption, and Personalization, held in Rome, Italy, in June 2013. The 21 long and 7 short papers of the research paper track were carefully reviewed and selected from numerous submissions. The papers cover the following topics: recommender systems, student modeling, social media and teams, human cognition, personality, privacy, web curation and user profiles, travel and mobile applications, and systems for elderly and disabled individuals.
Opinion-Driven Matrix Factorization for Rating Prediction -- Learning Likely Locations -- Evaluation of Attention Levels in a Tetris Game Using a Brain Computer Interface -- Comparing and Combining Eye Gaze and Interface Actions for Determining User Learning with an Interactive Simulation -- Inform or Flood: Estimating When Retweets Duplicate -- Understanding Email Writers: Personality Prediction from Email Messages.
Keywords: Computer science; Information storage and retrieval systems; Artificial intelligence; Computer Science; User Interfaces and Human Computer Interaction; Information Storage and Retrieval; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl. Internet).; e-Commerce/e-business.